2017
DOI: 10.1249/mss.0000000000001112
|View full text |Cite
|
Sign up to set email alerts
|

Sedentary Behavior, Physical Activity, and Abdominal Adipose Tissue Deposition

Abstract: Purpose We examined whether sedentary lifestyle habits and physical activity level are associated with abdominal visceral adipose tissue (VAT), subcutaneous adipose tissue (SAT), intermuscular adipose tissue (IMAT), and liver attenuation, independently of each other and potential confounders. Methods Analysis of 3,010 African American and Caucasian men and women, aged 42–59 years, from the Coronary Artery Risk Development in Young Adults (CARDIA) study who completed multiple-slice abdominal computed tomograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 32 publications
5
31
0
Order By: Relevance
“…In this cross-sectional study, adherence to MedDiet was not significantly related to this pathogenic fat depot. Results of this study on the negative association between total PA, in terms of total energy expenditure, and imaging defined VAT depot corroborate most of previous cross-sectional [3,32,33] and interventional studies [6,34], conducted among different populations of adults, using self-reported [33,35,36] and accelerometry-derived PA data [3,32].…”
Section: Discussionsupporting
confidence: 85%
“…In this cross-sectional study, adherence to MedDiet was not significantly related to this pathogenic fat depot. Results of this study on the negative association between total PA, in terms of total energy expenditure, and imaging defined VAT depot corroborate most of previous cross-sectional [3,32,33] and interventional studies [6,34], conducted among different populations of adults, using self-reported [33,35,36] and accelerometry-derived PA data [3,32].…”
Section: Discussionsupporting
confidence: 85%
“…These ndings are consistent with previous cross-sectional research in adult populations [3,32,40], which have found a hazardous relationship between SB and markers of body composition, including body fat, VAT and muscle mass [3,9,32,40,41]. The present results showed that greater SB is associated with greater body fat and lower muscle mass in an aging population, resulting in greater cardiometabolic risk and disability.…”
Section: Discussionsupporting
confidence: 93%
“…Mean educational attainment was 14.6 years. Average BMI in the sample was 27.5 kg/m 2 ; 25.6% were classified as obese, 25.4% were current smokers, and the sample had mean physical activity of 331 exercise units (which equates approximately to 30 min of moderate intensity activity 5 days a week (Whitaker, Odegaard, Jacobs, Sidney, & Pereira, ). Twenty‐six percent of men were heavier alcohol consumers (consumed at least 14 alcoholic drinks per week), and 20.0% of women were heavier alcohol consumers (consumed at least seven drinks per week) (Table ).…”
Section: Resultsmentioning
confidence: 99%